Pengaruh ROA, Keputusan Investasi, CR, TATO Dan Arus Kas Terhadap Return Saham Perusahaan Manufaktur - Nensi Ariani Guru Singa; Benny Rojeston Marnaek Nainggolan; Evaluasi Waruwu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
In Indonesia the development of the manufacturing industry is quite rapid, this can be seen from the development of manufacturing companies listed on the Indonesia Stock Exchange from year to year. This study aims to determine the effect of ROA variables, investment decisions, current ratio, TATO and cash flow on stock returns. The study population was obtained 143 companies selected using purposive sampling with certain criteria as many as 38 companies. The type of data used in this study is quantitative data. The data source in this study is secondary data. Data collection techniques were carried out with documentation and data analysis techniques using multiple linear analysis using the F test and t test at a significant level of 5% and the coefficient of determination. The results of the research partially indicate that ROA, investment decisions, current ratio and cash flow have no effect on stock returns. While TATO has an effect on stock returns. The results of the study simultaneously showed ROA, investment decisions, current ratio, TATO and cash flow affect stock returns. Keywords : Cash Flow, Current Ratio, Invesment Decisions, ROA, Stock Returns,TATO